A Constructive Approach for Colour Objects Sorting Robotics Model by Using Programmable Colour Light-To-Frequency Converter Method - Prasad Tripathy, Hara; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
A robotic model is basically a combination of mechanics and electronics, communally it is called as Mechatronics. The design and implementation of a robotic system is performed by comprising a coloured object detection and arranging it consequently. The tri-colour objects i.e. of Green, Blue and Red, are recognized by means of sensors. The arms of the robotics are controlled by multiple motor for separating them. Light to frequency converting technique is employed for detecting multi-coloured objects on the basis of programmable module such as TCS230. The robotic system as of autonomous that is capable of performing every activities by its own by supplying required power. The maximum employment of this type of robotics are in the industrial sector for automatic and intelligence working of machines.